CONFLICTS AND THEIR MANAGEMENT IN BUSINESS NEGOTIATIONS - Peleckis, Kęstutis; Peleckienė, Valentina; Peleckis, Kęstutis K. (IJRDO - Journal of Business Management, 2017)
Conflict analysis and their management showed that during the past decades its scientific understanding changed from the social sciences to interdisciplinary management fields. Conflicts are examined and defined in their own way by management, psychology, politics, law, economics and other sciences. Solutions of conflicts are an integral part of business negotiations – in negotiations are solved various inconsistencies, conflicts of both negotiating parties. Conflict resolution techniques can change in dependence on the culture of the country. In negotiations with the representatives of other countries is necessary to know the dominating conflict management styles in the relevant country and how it is possible to adjust own behavior. A significant number of modern business negotiations are international, so it is proposal to use mediator in negotiations of another culture who is an individual having the same cultural experience as business partners. In process of preparation for negotiations with other country is necessary to take into account the characteristics of relationships prevailing in that country. This paper reviews the process of conflicts in negotiations and their prevention in the interaction of different cultures. Also this paper analyzes the impact of exchange of information and management of expectations for the prevention of conflicts in the negotiations. In order to manage the expectations of the other side of the negotiations is necessary to find out in the preparation phase the values of partner, and try to manage information in negotiations, understanding the values and the context of the other side of negotiations, in order to form useful for us expectations from the other side, which would help to avoid further conflicts in the negotiating process.